The Creation of the Manik Pangaras Dance A Form of Acculturation of Two Balinese and Chinese Cultures - I Nyoman Agus Hari Sudama Giri; I Nyoman Resa Angga Nurbawa (Acintya, 2025)
Manik Pangaras is a dance work inspired by the acculturation of two cultures, namely Balinese and Tionghoa (Chinese). This story is found in the babad wich tells of the union of love the Balinese king named Sri Jaya Pangus and Kang Cing Wie (now in Balinese still worshipped as the figure of Ayu Mas Subandar). Conceptually, this work is more focused on the unification of the breath of two cultures, through research, exploration of the techniques of various movements in the dance of two cultures, as well as empirical experience and body aesthetics. The Nolin instrument as one form of cultural acculturation, is used as an accompaniment in this work. Collaborating with the Neo Nolin Community, this first dance work with Nolin accompaniment requires a unification of thought and a fairly long process. The Manik Pangaras dance work refers to the meaning of the massage to be conveyed, referring to the harmonization of the unification of the breath of two cultures, protected by the umbrella of unity, namly tolerance and matual support. The procces of creating this work uses the “Padu Rasa” method, proposed by I Nyoman Agus Hari Sudama Giri in his book, “Tapak Samar”. This method refers to the system of combining or marryng artistic elements. It consists of seven step, know as “Pitung Tindak”, namely: Nureksain (description), Nglaca-laca (concept), Tategar (experimentation), Pilah-pilih (sorting and selecting), Mupulang (collecting), Ngawangun (Composing and realizing), and Nelesin (evaluation, deepening the sense of movement and expression). The Manik Pangaras dance, performed by five female dancers, has a duration of approximately 8 minutes and 30 seconds. The performance consists of three parts: part 1 depicts the beginning of the unifications, part 2 contains the choreography of the fan game, and part 3 depicts the umbrella game scene.